Puncture biopsy of parietal pleura - Orellana Muñóz, José Luis (1962)
The results of 20 biopsies of parietal pleura puncture performed in 17 patients, using the method of Francis with some modifications is presented. In 17 cases (85%), adequate sample for pathologic examination, which revealed pleurisy Tuberculosis in ten cases, two Metastatic Neoplasms and Chronic nonspecific Pleuritsi in the remaining five was obtained.